KONSEP SEKSUAL DALAM ISLAM - Imam Zarkasyi Mubhar (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2021)
When we talk about sexuality, it is often misinterpreted as a conversation that is primarily about sex. Meanwhile, the extent of the discussion of sexuality is broader than just the issue of sex, which is more offensive to the organic angle. Sexuality is the way a person meets, appreciates, and communicates his thoughts as a sexual being. Overall, it concerns how a person uses his soul, making use of his feelings and actions depending on his situation as a sexual being. This paper discusses the idea of ​​sexuality in Islam, the focus of the study is on sexuality in Islam. The formulation of this paper; First researching sexuality, there are people who react separately (actually) not as far as scholastic, also concentrating on sexuality will increase a person's capacity to be more subtle and careful in sexual relations with their partners. Issues in sexuality are about the notion of sexuality, the organization and the notion of sexuality in the Qur'an. The sex that is allowed and guaranteed by standards, religion and law is hetero provided that they must marry. For a while, there was another trend, namely a certain homosexuality. Gay people are not recognized in the public arena, especially tight networks. Islam has regulated things that are identical with sexuality, Islam gives space to heteros, on the grounds that it is sunnatullah. While homosexuality, both gay and lesbian, is a fahishah (terrible) act, such demonstrations are haram.